Determination of the efficiency of the type Sinorhizobium meliloti L the formation of root nodules on different Medicago sativa varieties - Raghad Al-Zaidy; Najwa Ibrahim; Abdullah Al-Niemi (College of Education for Pure Sciences, 2021)
This study was carried out in the laboratories of the Research Unit of the Department of Biology / College of Education for Pure Sciences / University of Mosul/Iraq. Sinorhizobium meliloti bacteria were isolated from the root nodes of alfalfa plants cultivated in two areas of Nineveh Governorate, which are the wire house in the College of Education / University of Mosul and a farm belonging to Hawi  Alkanesa Mosul/Iraq.  , isolation of four isolates of Sinorhizobium meliloti from the root nodules formed on four species of Medicago sativa (Iraqi, Belgian, Pakistani and American varieties)and giving them the symbols Rh1, Rh2, Rh3 and Rh4. The isolates were diagnosed based on the phenotypic traits, their susceptibility to staining with Gram stain, agricultural characteristics, the biochemical and biological tests.  The results showed that the highest susceptibility of rhizobal isolates to infecting a specific genotype (the plant host) from which they were isolated, which is due to the extent of compatibility between them represented by the success of infection and the formation of root nodules, and its development on the specialized host. All isolates (Rh4, Rh3, Rh2 and Rh1) of  E. meliloti showed the ability to form root nodules on the roots of the seedlings of the four varieties with variation in the efficiency of these isolates ,The isolates (Rh1)  as recorded the highest percentage of infection, which reached to 68%, followed by isolates (Rh2) and reached to 64% which was reflected in the rate of increase in average of the number of nodules / seedlings, which ranged between (2-3.25) and the high protein content of the pollinated seedlings which average ranged between (3.9 - 4.1) mg / gm, and  accompanied by an increase in the rate of the number of vegetative branches therein.